Vídeo educativo sobre o uso de medicamentos para a pessoa idosa - Andrade, Priscilla Leite Costa (2021)
Introduction: The growing number of elderly people is associated with a greater need for health services, in particular, the use of medication. The aging process is usually accompanied by chronic diseases, comorbidities and polypharmacy, therefore, health professionals should pay attention to the proper use of medicines by the elderly. Resources that favor adherence and correct use of medications are valid and desirable, videos are easily accessible tools and can help in this context. Objectives: to prepare an Integrative Literature Review on the use of medication in the elderly in Primary Health Care; analyze the factors that interfere with adherence to medications used by the elderly in a Basic Health Unit in the city of Bayeux-PB and build an educational video with guidelines for the use of medications by the elderly. Method: an exploratory study of mixed approach with elderly people using various medications, members of the coverage area of a Basic Family Health Unit, from January 2021 to March 2021, in the city of Bayeux-Paraíba. To analyze the profile of the participants, the Mini Mental State Examination was used first, in addition to a sociodemographic questionnaire and a semi-structured questionnaire on medications used. The information obtained was processed with the help of the IRAMUTEQ 0.7 alpha 2 software. Results: regarding the sociodemographic profile, the majority were women (80%), between 60 and 69 years old, equally had incomplete elementary education and higher education (36%); income from 1 to 3 minimum wages, catholics, married, with their own house and living with their spouse. About medication consumption, the average was 3.4 per day, with regulators of the cardiovascular system being the majority. In the analysis, there was an association between the classes: “safety of medication use”, “purpose of medication” and “possible effects of medication”. The classes: “most used medications” and “medication dosage” were directly related. From the results obtained, an educational video was created with information about the guidelines regarding the proper use of medication by the elderly. The video addressed the guidelines on effective communication in the prescription and purchase of the drug, as well as the dosage and general guidelines needed to use the medication properly. Adobe Photoshop version 2021 was used in the production of the media. Adobe AfterEffects version 2020 was used to develop the art and to make all graphic animations. Conclusion: With this research, it was possible to observe the need to expand the guidelines as far as the use of medicines in the long-lived population and educational videos may help in this process, but not only this type of technology, more effort is needed on the part of health promoters in order to expand the scope of educational actions in health for the elderly.